Using Different Types of Exercise Can Have Varied Effects on Fat Mass and Muscle Mass in Obese Females - Purwo Sri Rejeki; Adi Pranoto; Raden Argarini; Faiq Amirul Hakim; Muhammad Nazmuddin; Teus van Laar; Maxime Boidin (Physical Education Theory and Methodology)
Objectives. This study aimed to compare the effects of aerobic and resistance training on improving body composition in obese women.